Under Control: A Control Theory Introduction for Computer Scientists - Guilloteau, Quentin; Cerf, Sophie; Bleuse, Raphael; Robu, Bogdan; Rutten, Eric (2024 IEEE International Conference on Autonomic Computing and Self-Organizing Systems Companion (ACSOS-C), 2024)
This hands-on tutorial aims at introducing the basis of Control Theory, applied to the runtime management of computing systems, through a practical example. This tutorial is composed of two parts. In the first part, we present the motivation and classical tools of Control Theory: formulation, modeling, and controllers. During the second part, the participants will experiment with the concepts presented in the first part through interactive computational documents, via a Jupyter Notebook. Attendees will need a computer with an internet connection and a "recent" web browser, and only basic programming knowledge. The tutorial is available at the following URL: https://control-for-computing.gitlabpages.inria.fr/tutorial/